The Magnetic Origin of the Mystery of Rare Hα Moreton Waves - Ze Zhong; Yao Chen; Y. W. Ni; P. F. Chen; Ruisheng Zheng; Xiangliang Kong; Chuan Li (The Astrophysical Journal)
Over the past three decades, a lot of coronal fast-mode waves have been detected by space missions, but their counterparts in the chromosphere, called Moreton waves, have rarely been captured. How this happens remains a mystery. Here, to shed light on this problem, we investigate the photospheric vector magnetograms of the Moreton-wave events associated with M- and X-class solar flares during 2010–2023. The H α data are taken with the Global Oscillation Network Group and the Chinese H α Solar Explorer. Our statistical results show that more than 80% of the events occur at the edges of active regions and propagate nonradially, due to asymmetric magnetic fields above the flares. According to the reconstructed magnetic field and atmospheric model, Moreton waves propagate in the direction along which the horizontal fast-mode wave speed drops the fastest. This result supports the inclined magnetic configuration of the eruption being crucial for generating Moreton waves, even for X-class flares. It may explain the low occurrence rate of Moreton waves and why some X-class flares accompanied with coronal mass ejections do not generate Moreton waves.